Results of surgical treatment of patients with ruptured anterior communicating artery aneurysms - I. O. Shkil (Сучасні медичні технології)
Anterior communicating artery aneurysms (AComA) are the most common type of intracranial aneurysms, accounting for approximately 35 % of all ruptured intracranial aneurysms.